Local Wisdom-Led Business Communication: A Case Study of “Barosok” in Livestock Market in West Sumatera Indonesia - Evanita, Susi; Andriani, Chichi; Asri, Zul; Trinanda, Okki; Fahmi, Zul (Humanus, 2024)
Business communication with local wisdom of ethnic Minangkabau in addition to aiming for business interests but still prioritizing social and human values. This research aims to reveal the non-verbal symbols used in the "barosok" tradition as one of the communication styles of the livestock trade in the West Sumatra region, especially the Minangkabau ethnics and documented it in a book. This communication style upholds the values of privacy, confidentiality, solidarity, and tolerance. This research was conducted using the Qualitative method with an Indept interview approach, the informants of this research were traders and community leaders in the Talao Guguak Bukittinggi livestock  market area and  the  Muaro  Paneh  Solok  livestock market. Informants were drawn using the snowball sampling method with data collection techniques using triangulation. This research concludes that: two regions in West Sumatra still have traditional buying and selling transactions (barosok), namely Talao Guguak Bukittinggi and Muaro Paneh-Solok cattle market, it is hoped that there will be an increase in understanding and preservation of traditional business communication (barosok) for the people of West Sumatra in particular and the people of Indonesia in general, and the results of new research in the form of data collection/documentation of research objects. This research recommends relating to the effectiveness of this communication model in achieving business goals and the current generation's perception of it.